Video-lectures: An effective complementary teaching method at business college - Vadnjal, Jaka (Serbian Journal of Management, 2017)
A new teaching methodology was tested at a private college, which delivers business  studyprograms on the undergraduate and graduate level. The combination of video-lectures with live classactivities (discussions, case study solving) was used in the course which provides studentscompetences for managing growing small and medium-sized business. Full- and part-time studentsparticipated in the two separated classes with identical study program and the same methodologicalapproach was applied to assess the teaching approach. The main objective of the study was toexamine the possible differences between the two groups of studies. In total 126 students participatedin the study and the data collection was done with a survey. Several statistically  significantdifferences were revealed. The most important finding is that part-time students were much lessenthusiastic for the delivered teaching approach. It looks like they appreciated more the liveinteraction with other students and with the teacher and probably saw the opportunity of activeparticipation as the main added value of the studies. The implication of the study is that coursedesign, which includes video, should carefully take into account the two types of students addressed.
Keywords: BUSINESS AND ADMINISTRATION STUDIES; video lectures; e-learning; teaching methods; STUDENT PARTICIPATION; METHODOLOGY